Strength and ductility improvement of recycled aggregate concrete by polyester FRP-PVC tube confinement. (1st April 2019) - Gao, Chang; Huang, Liang; Yan, Libo; Jin, Ruoyu; Kasal, Bohumil
Abstract: In literature, studies on recycled aggregate concrete (RAC) with recycled aggregates (RAs) originated from clay brick waste are rare, which is mainly attributed to the much lower compressive strength of the RAC with recycled clay brick aggregates (RAC-RCBA) when comparing with its normal aggregate concrete (NAC) counterpart. Nowadays it is well known that fiber reinforced polymer (FRP) composites as lateral confining materials can improve the strength and ductility of NAC significantly. In this study, FRP confining materials were used to improve the compressive strength and ductility of the RAC-RCBA. Compared with conventional synthetic glass or carbon FRP composites, polyester FRP (PFRP) and Polyvinyl chloride (PVC) are much cheaper and show much larger tensile deformation capacity. Therefore, this study investigated the axial compressive behavior of PFRP and PVC hybrid tube encased RAC-RCBA (i.e., shortened as PFRP-PVC-RAC-RCBA) structure. This PFRP-PVC-RAC-RCBA system consisted of an RAC-RCBA core, encased by a PVC tube directly and the PVC tube was further confined with a PFRP tube (i.e. PFRP tube-PVC-RAC-RCBA specimen) or PFRP strips (i.e. PFRP strip-PVC-RAC-RCBA) at the outermost layer. Uniaxial compression tests were performed on 33 PFRP-PVC-RAC-RCBA and 39 unconfined RAC-RCBA specimens to evaluate and compare the axial compressive behavior of PVC tube encased RAC-RCBA, PFRP tube encased RAC-RCBA, PFRP tube-PVC-RAC-RCBA and PFRP strip-PVC-RAC-RCBA columns. The tested variables included the number of PFRP layers (3-, 6- and 9-layer), the type of PFRP confinement (in the configuration of tube or strips) and the spacing of the PFRP strips (25 and 50 mm). The tested results demonstrated that the PFRP-PVC hybrid confining system enhanced the compressive strength and axial and lateral deformations of the RAC-RCBA pronouncedly, e.g. the increase in strength ranged from 4.5% to 39.6%. The enhancement in strength and deformations was increased with a thicker PFRP tube or strip. Both the PFRP tube-PVC-RAC-RCBA and PFRP strip-PVC-RAC-RCBA showed the similar axial compressive stress-stain behaviors. In addition, the comparison of PFRP tube-PVC-RAC-RCBA with the glass/carbon FRP tube-RAC-RCBA indicated that the GFRP and CFRP tube confinement resulted in much larger enhancement in ultimate compressive strength of RAC-RCBA due to the much larger tensile modulus and strength of these G/CFRP composites. However, PFRP-PVC tube confinement led to much larger axial deformation of the RAC-RCBA compared with the G/CFRP tube confinement due to the much larger tensile strain of the PFRP and PVC material. Furthermore, design-oriented compressive stress-strain models were developed for PFRP-PVC-RAC-RCBA specimens.